Meningkatkan Kemampuan Menceritakan Kembali Kisah Tokoh-Tokoh Perjanjian Lama Melalui Kombinasi Metode Show And Tell Dan Model Pembelajaran Problem-Based Learning (PBL) Pada Peserta Didik Fase A Kelas 2 SDN 077285 Afia - Jika Serasih Ziliwu (Sekolah Tinggi Pastoral Kateketik (STPKat) Santo Fransiskus Assisi Semarang, 2024)
This study aims to improve students' ability to retell the stories of Old Testament characters through a combination of the Show and Tell method and the Problem-Based Learning (PBL) learning model in class 2 of SDN 077285 Afia. The Show and Tell method provides students with the opportunity to express their understanding of the material in a creative way, while PBL stimulates critical and collaborative thinking skills through solving real problems. This study uses a quantitative approach with a classroom action design, which involves data collection through observation, testing, and interviews. The results show that the combination of these two methods is significant in improving students' ability to retell the stories, as well as increasing student engagement and motivation to learn. This study concludes that the application of the combination of the Show and Tell and PBL methods is effective in learning, especially in the context of religious education.